Pola Hidup Konsumtif Masyarakat Penerima Bantuan Program Keluarga Harapan (PKH) (Studi Kasus di Desa Mojodeso, Kecamatan Kapas, Kabupaten Bojonegoro) (Administratio, 2020)
This study aims to determine the consumptive actions practiced by the Hope Family Program beneficiaries. This study uses a qualitative approach with the perspective of Baudrillard's theory. Informants were selected using a purposive sampling technique. Data analysis and interpretation techniques were carried out with a deeper understanding. Consumptive behavior practiced by PKH recipient communities is demonstrated through consumption or shopping activities based on desire, not based on needs. These actions were found in activities, including: (1) Women beneficiaries of PKH assistance more often spend the funds received within two to three days, (2) the funds are used to shop for large amounts of consumption materials, ( 3) besides that it is also used to buy household furniture such as cooking utensils. To control the use of funds to PKH recipient communities, the village government held a socialization program which was held once a month. The conclusions of this study are: (1) The theory of consumptive society Jean Baudrillard is shown by the shopping practice of PKH members who buy on the basis of desires, not based on needs, (2) PKH members do not have knowledge of economic literacy so that they have consumptive behavior in using PKH funds Therefore, the village government needs to provide understanding related to economic literacy in the socialization program.